IMPLEMENTATION OF INCLUSION IN HIGHER EDUCATION - Fedotenko, Inna; Yugfeld, Irina (Student Niepełnosprawny. Szkice i Rozprawy, 2021)
The authors consider the ways and means of implementing the idea of inclusion in the university educational process. The researchers have included information on the history of inclusion, on various models of inclusive education, and on the specifics of a family with a child with special educational needs in the content of psychological and pedagogical disciplines, as well as elective courses. The authors have introduced new tasks of teaching practice, with students describing conflicts, bullying, mobbing, and school violence in traditional and inclusive classrooms. Stu-dents have been asked to justify their intended actions, which could prevent potential risks and find a competent way out of a difficult situation. Plot-role-playing games and group discussions held in student groups on the problems of "special" children and migrant schoolchildren have also facilitated implementation of the idea of inclusion. Discussion teaches future teachers to coordinate positions, values, to make decisions, and helps them see new personal meanings. Students' daily communication at the university with physically or mentally challenged mates with students of different cultures, faiths, and languages has played a significant role in their acceptance of inclusion.